Designing a Standardized Marking System for Public Service Drones - Hagberg, David; Petterzon, Filippa (My University, 2025)
The increasing interest in drone innovation for public services, such as emergency medical deliveries and early situational awareness, raises new challenges around public trust and transparency. This thesis, conducted in collaboration with Region Västra Götaland (VGR), investigates how a standardised marking system can help communicate the purpose and origin of public service drones to the general public. By aligning the needs of diverse stakeholders, including VGR, drone companies, and citizens, the study aims to reduce ambiguity and increase acceptance of drones into shared public spaces. Using methods including interviews, questionnaires, and iterative prototyping, the project identifies key concerns around surveillance, recognition, and ethical concerns. The resulting design framework, MarkeD, including visual markings such as colour schemes, patterns, and placements of logos, is intended to signal trustworthiness and to differentiate drones from private or military use, as well as support visibility. The findings offer both a practical framework for drone marking and broader insights into designing for societal acceptance in emerging technologies as well as academic discourse on new and controversial technologies.
Keywords: Drones, UAV, Human-Drone Interaction, Healthcare, Innovation, Interaction Design, Public Perception, Visual Markings, Explicability and Trust